2014
DOI: 10.1126/science.1250551
|View full text |Cite
|
Sign up to set email alerts
|

The Gravity Field and Interior Structure of Enceladus

Abstract: The small and active Saturnian moon Enceladus is one of the primary targets of the Cassini mission. We determined the quadrupole gravity field of Enceladus and its hemispherical asymmetry using Doppler data from three spacecraft flybys. Our results indicate the presence of a negative mass anomaly in the south-polar region, largely compensated by a positive subsurface anomaly compatible with the presence of a regional subsurface sea at depths of 30 to 40 kilometers and extending up to south latitudes of about 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
431
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(457 citation statements)
references
References 34 publications
25
431
0
1
Order By: Relevance
“…On the other hand, the interiors of the Saturnian satellites are still not entirely understood. Some suggest that there is an internal global ocean under Enceladus' icy shell (Nimmo & Pappalardo 2006;Lainey et al 2012), others suggest a subsurface "sea" localized in its south polar region (Collins & Goodman 2007;Iess et al 2014). Meanwhile, the physical forced libration measurements (Tajeddine et al 2014) suggest that Mimas has a more complex Full Table 1 is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/575/A73 interior than was previously believed and may have a subsurface ocean.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the interiors of the Saturnian satellites are still not entirely understood. Some suggest that there is an internal global ocean under Enceladus' icy shell (Nimmo & Pappalardo 2006;Lainey et al 2012), others suggest a subsurface "sea" localized in its south polar region (Collins & Goodman 2007;Iess et al 2014). Meanwhile, the physical forced libration measurements (Tajeddine et al 2014) suggest that Mimas has a more complex Full Table 1 is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/575/A73 interior than was previously believed and may have a subsurface ocean.…”
Section: Introductionmentioning
confidence: 99%
“…This is also confirmed by the ratio of (b-c) / (a-c) = 0.41, obtained in our study, far from the hydrostatic equilibrium ratio of 0.25. In other research, Iess et al (2014) suggested that the core is in hydrostatic equilibrium, and that an ice layer is in the isostatic. A more accurate model of the internal structure of Enceladus, consisting of a core, water and ice layers (with thickness decreasing towards the poles), was proposed by McKinnon (2015).…”
Section: Resultsmentioning
confidence: 97%
“…In this sense, the discovery of geological evidence pointing to the possibility of water running on ancient Mars (Squyres et al, 2004), or the emissions detected on Enceladus as evidence for the existence of internal water pockets (Iess et al, 2014), place some of the objects in the Solar System as important targets for astrobiological studies. One of the most significant results of the Galileo orbiter mission was the discovery of geological features on the surface of Europa (Pappalardo et al, 1999), the smallest of the four Galilean satellites that suggested the existence of an aqueous layer beneath an icy water crust.…”
Section: Introductionmentioning
confidence: 99%